2021
DOI: 10.1002/solr.202100128
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Engineering via Self‐Assembled Thiol Silane for High Efficiency and Stability Perovskite Solar Cells

Abstract: Self‐assemble monolayer (SAM) has been proven to be an effective interfacial layer to improve the performance of perovskite solar cells (PSCs). Herein, a 3‐mercaptopropyltrimethoxysilane (MPTMS) SAM is used as an interlayer between the SnO2 electron‐transporting layer (ETL) and the perovskite film to modify fully air‐processed PSCs. In the devices prepared by the two‐step method, this MPTMS SAM interlayer can slow down the crystal growth of perovskite and smooth the surface of the SnO2 ETL, which could induce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 47 publications
0
25
0
Order By: Relevance
“…[112] SAMs consisting of silane also have been used to enhance device efficiency and stability through passivation of defects and enhanced interfacial adhesion. [114] Yang et al reported that SnO 2 with a silane-based SAM (3-aminopropyltriethoxysilane) can provide better surface wetting property, resulting in more intimate contact between SnO 2 and perovskite with improved perovskite morphology. [115] The silane groups also passivate the defects by reacting with OH groups on SnO 2 , leading to a lower defect concentration and charge recombination.…”
Section: Functional Organic Compoundsmentioning
confidence: 99%
“…[112] SAMs consisting of silane also have been used to enhance device efficiency and stability through passivation of defects and enhanced interfacial adhesion. [114] Yang et al reported that SnO 2 with a silane-based SAM (3-aminopropyltriethoxysilane) can provide better surface wetting property, resulting in more intimate contact between SnO 2 and perovskite with improved perovskite morphology. [115] The silane groups also passivate the defects by reacting with OH groups on SnO 2 , leading to a lower defect concentration and charge recombination.…”
Section: Functional Organic Compoundsmentioning
confidence: 99%
“…The perovskite light-absorbing layer prepared by the solution method may have considerable defects, which not only become the center of carrier recombination, leading to a decrease in device efficiency but also easily cause device degradation, reducing the stability the devices. [126][127][128][129][130][131][132] Zhou et al [19] introduced inorganic Eu 3þ -Eu 2þ ion pair in PbI 2 solution. The results showed that the Pb 0 and I 0 defects in the perovskite were passivated during the redox process of europium (Figure 7a,b).…”
Section: Additives In Inorganic Componentsmentioning
confidence: 99%
“…8d). 81 The average PCE of such PSCs utilizing MPTMS was significantly increased from 16.62% to 18.75% in the device prepared via a two-step process. The modified PSC obtained a maximum efficiency of more than 20% with favorable stability in ambient air (Fig.…”
Section: Interfacial Engineering In the Normal Structurementioning
confidence: 94%